Effects of SMOF on soil properties, root-zone microbial community structure, metabolites, and maize (Zea mays L.) response on a reclaimed barren mountainous land - Li, Xuqing; Wang, Daoze; Lu, Qiujun; Tian, Zhongling; Yan, Jianli (Frontiers in Microbiology, 2023)
Maize is the largest crop produced in China. With the growing population and the rapid development of urbanization and industrialization, maize has been recently cultivated in reclaimed barren mountainous lands in Zhejiang Province, China. Nevertheless, the soil is usually not suitable for cultivation because of low pH and poor nutrients conditions. To improve the quality of the soil to meet the requirement of crops, inorganic, organic, and microbial fertilizers were used in field. Among them, organic fertilizer based sheep manure had a great beneficial effect on improving soil quality and had been widely applied in reclaimed barren mountainous land. In order to systematically evaluate the effect of SMOF on reclaimed barren mountainous land, the soil properties, root-zone microbial community structure, metabolites and maize response were investigated. Results of this study showed that the application of SMOF not only significantly modified the soil physical, chemical and biological properties of reclaimed barren mountainous land but also promoted maize growth. SMOF can be used as a good amendment for maize production in reclaimed barren mountainous land.